Unlikely Beginnings : A Soldier's Life - Mitha, A. O. (Karachi Oxford University Press, 2007)
Fazal Mahmood was Pakistan's first cricketing hero, a pace bowler who could bowl on any surface, particularly feared for his deadly leg-cutters. In his autobiography he describes the triumphs and tribulations of Pakistan's first cricket team and discusses bowling technique and the sport in general.
Include Index, Appendix, Abrivations and Illustrations.
Keywords: Soldiers -- Pakistan